2014
DOI: 10.1080/19476337.2014.941411
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of chemical composition, color, and thermal gelling properties of normal and PSE-like chicken breast meat

Abstract: The objective of this study was to evaluate the differences between normal and pale, soft, exudative (PSE)-like chicken breast meat in the chemical composition, pH, color, water binding capacity, textural properties, salt-soluble protein (SSP) extraction as well as dynamic rheological properties. Compared with normal meat, PSE-like chicken meat showed similar moisture, fat, and ash content (P > 0.05), but significantly lower protein content (P < 0.05). It had a significantly higher L* and lower pH and SSP extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 48 publications
5
14
0
Order By: Relevance
“…These results are similar to the findings reported by Qiao et al (2002) and Li et al (2014), who reported PSE broiler breast meat containing less protein content than normal colored meat. Qiao et al (2002) reported significant differences in protein content between normal and pale broiler breast meat (22.96% vs. 22.58%).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These results are similar to the findings reported by Qiao et al (2002) and Li et al (2014), who reported PSE broiler breast meat containing less protein content than normal colored meat. Qiao et al (2002) reported significant differences in protein content between normal and pale broiler breast meat (22.96% vs. 22.58%).…”
Section: Discussionsupporting
confidence: 82%
“…No differences were observed between normal and pale groups in ash (%), dry mater (%), and total lipid contents in this study ( Table 2). The closest values to these results were reported by Qiao et al (2002) and Li et al (2014).…”
Section: Discussionsupporting
confidence: 72%
“…Group mean values of water and lipid content of meat samples ranged from 69.23% to 71.43% and from 8.55% to 13.05%, respectively (Table 2), which is in accordance with previous reports (Durek et al, 2014;Li et al, 2015). The values measured for water and lipid indicated that the geographical origin did have an influence on meat composition.…”
Section: Meat Compositionsupporting
confidence: 81%
“…Moisture content was determined in triplicate according to the reference (Li et al, 2015). The dried meat of 10 g was defatted by Soxhlet extraction using ether for 6h to obtain the protein; in the meantime, fat content was determined by the extraction system.…”
Section: Sample Pretreatmentmentioning
confidence: 99%
“…Water content was determined in triplicate according to the reference (Li et al 2015). The samples were surface decontaminated by three consecutive rinses in double-deionized water and stored in plastic bags at −20°C until freeze-drying (freeze dryer FD-1C-50, Beijing Boyikang Instrument Company, China).…”
Section: Sample Preparationmentioning
confidence: 99%